Cardiovascular remodeling induced by passive smoking - Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (My University, 2009)
Coronary heart disease (CHD) is the most common cause of death in many developed countries. The major risk factors for CHD are smoking, high blood pressure, diabetes, high cholesterol levels, and lack of physical activity. Importantly, passive smoke also increases the risk for CHD. The mechanisms involved in the effects of passive smoke in CHD are complex and include endothelial dysfunction, lipoprotein modification, increased inflammation and platelet activation. Recently, several studies have shown that exposure to tobacco smoke can result in cardiac remodeling and compromised cardiac function. Potential mechanisms for these alterations are neurohumoral activation, oxidative stress, and MAPK activation. Although the vascular effects of cigarette smoke exposure are well known, the effects of tobacco smoking on the heart have received less attention. Therefore, this review will focus on the recent findings as to the effects of passive smoking in acute and chronic phases of vascular and cardiac remodeling. © 2009 Bentham Science Publishers Ltd.
Keywords: gelatinase A; gelatinase B; mitogen activated protein kinase; mitogen activated protein kinase 1; mitogen activated protein kinase 3; tobacco smoke; cardiovascular disease; cardiovascular remodeling; echocardiography; endothelium; environmental exposure; human; inflammation; nonhuman; oxidative stress; passive smoking; review; thrombocyte activation; vascular disease; Animals; Coronary Disease; Coronary Vessels; Heart Ventricles; Humans; Inflammation Mediators; Metalloproteases; Platelet Activation; Protein Kinases; Risk Factors; Tobacco; Tobacco Smoke Pollution